Self-Ordered Ge Nanodot Fabrication by Using Reduced Pressure Chemical Vapor Deposition. (1st January 2019) - Yamamoto, Y.; Itoh, Y.; Zaumseil, P.; Schubert, M. A.; Capellini, G.; Washio, K.; Tillack, B.
Abstract : Ge nanodot formation on Si surface and its three dimensional alignment is investigated using a reduced pressure chemical vapor deposition system. By exposing GeH4 on Si (001) surface at 550°C, a smooth wetting Ge layer is deposited for the first ∼0.9 nm, and then Ge nanodot formation occurs according to a Stranski-Krastanov growth mechanism. The Ge nanodots are randomly distributed with density of ∼6 × 10 10  cm −2 . By postannealing at 600°C, the Ge nanodots are coalesced. The size and density become ∼60 nm diameter 5 nm height and ∼1.5 × 10 10  cm −2, respectively. By exposing GeH4 followed by postannealing at 600°C on checkerboard mesa structured Si surface which is fabricated by embedded body-centered tetragonal (BCT) Si0.6 Ge0.4 nanodots, the Ge nanodot formation occurs at concave regions of the checkerboard mesa. By repeating Ge nanodot formation followed by Si spacer deposition by two step epitaxy using SiH4 at 600°C and using SiH2 Cl2 at 700°C, vertical alignment of the Ge nanodots is observed. The lateral periodicity of the Ge nanodots is the same as that of the BCT Si0.6 Ge0.4 nanodot template. The driving force of the self-ordered alignment is tensile strain of Si spacer surface above the Ge nanodots. By using the checkerboard mesa structured Si substrate by embedded BCT Si0.6 Ge0.4 nanodot stack deposition as a template, vertically and laterally aligned 3D Ge nanodot stack fabrication is demonstrated without photolithography process.